Pendapat Pemilik Usaha-Usaha Kuliner Di Jakarta Terhadap Peran Go-Food Dalam Pengembangan Usahanya - Octarini Octarini; Eko Harry Susanto (Universitas Tarumanagara, 2019)
The rapid change of technology has a massive impact in all kinds of culinary business in Jakarta. This research will describe opinions from culinary businesses in Jakarta regarding the existence of Go-Food as a tool to develop their business. What role does Go-Food play as a tool for their business strategy, the changes they experience after they cooperate the business with Go-Food, and what are their opinions about the best strategy for their cooperation to achieve maximum benefits for every party. This research is using a qualitative descriptive method. The results of this research shows that Go-Food does not bring many influences for well established businesses that had been around for many years, on the contrary in new businesses Go-Food bring a massive impact. Some changes are positive and some are negative. The positive sides are growth of profit and turnover, expanding product delivery range, brand awareness and brand exposure. The negative side is the increases of product price appeared in Go-Food application. At the end of this research every party agree that Go-Food has given a good service for its customers and all culinary businesses whom Go-Food has collaborated with.